Tragedy, modernity and mourning - Taxidou, Olga (Edinburgh University Press, 2004)
This powerful reinterpretation of Greek tragedy focuses on the performative - the physical and civic - dimension of tragedy. It challenges the idealist, humanist, and universalist approaches that have informed our most cherished philosophical, psychoanalytical, and modern interpretations of Greek tragedy and, in doing so, asks us to renew our relation to these works and to our literary and philosophical inheritance. The book reassesses tragic form in relation to Athenian democracy and links it with a performative discourse that both excludes the feminine and relies on civic and private forms of mourning. At the same time, it explores the centrality of tragedy for thinkers of Modernity such as HÜlderlin, Nietzsche, Hegel, Freud, Brecht and Benjamin. Through a persuasive analysis of both classical theorists - Plato and Aristotle - and modern theorists - Benjamin, Lacan, Kristeva, Derrida and Butler - the book significantly shifts the emphasis from a Sophoclean model of tragedy to a Euripidean one. Close readings of the performance aspects of Greek play-texts help illuminate these ideas. Features Compelling new interpretation of Greek tragedy Performance based Attentive to issues of gender